Development of Interactive Animation Videos for Civics Learning to Improve the Critical Thinking Abilities of Elementary School Students - Ningsih, Atiya; Udin, Tamsik; Arifuddin, Ahmad; Lubis, Maulana Arafat (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study changed the low critical thinking skills of students caused by students not being accustomed to being trained with indicators in students' critical thinking. To overcome this problem, researchers developed interactive animated video media in Civics learning to improve students' critical thinking skills. This study aims to develop valid and practical interactive animated video media to improve critical thinking skills of grade IV elementary school students. This research uses the Research and Development (R&D) method with the ADDIE model. The data collection techniques used in this study were validation sheets, and practicality questionnaires. The subjects of this study were 23 fourth grade students of Pelandakan 2 State Elementary School in Cirebon City. The results showed a media expert score of 97.22% with the category